Are you looking for the value of n?
after multiplying both sides by 2, the equation will look
add like terms
add 3 to both sides
divide both sides by 3
In the parenthesis you can simplify to:
Multiply both sides by 2
Add 3 to both sides
Divide both sides by 3
first you change the "/2" from side which should now multiply... (2n-3+n)=3*2
Remove the parenthesis now and multiply... 2n-3+n=6
Now change the -3, it will add now... 2n+n=6+3
Do the math... 3n=9
Now move the 3, it is multiplying so no it will divide... n=9/3
and done ... n=3
lets check... (2(3)-3+(3))/2=3
All you would do is multiply both sides by 2 to get rid of the divided by two. That would leave you with 2n-3+n=6. You would then add the n's together to get 3n-3=6. Then you add 3 to both sides to cancel the minus three. That leaves you with 3n=9 which means that n=3.
Ur question is (2n - 3 +n) / 2=3,right
OK so u need to cross multiply the denominator of LHS with the numerator of RHS,like this
2n-3+n=2 x 3
Then do the following :-
2n - 3 +n=6
Then collect the like terms
Then add the like terms
Then divide by bringing 3 on RHS side
So ur answer is 3
if u liked my procedure ,plzzzz choose my answer to be the best answer.
This article contents is post by this website user, EduQnA.com doesn't promise its accuracy.
More Questions & Answers...